Comercio y ferias de trueque: España y los indios de Nuevo México - Flagler, Edward K. (Revista Española de Antropología Americana, 2007)
This paper describes commercial relations between the Spanish and the Indians of New Mexico between the late 17th and early 19th centuries. Mentioned are some of the fairs that took place in Taos, Pecos and other towns and how they were replaced by others as the frontier of the province advanced towards the east. Of special importance is the interrelationship that developed between the Pueblo Indians, the nomadic tribes, and the Spanish. Another factor was the influence of the French who established trade relations with some of the Plains tribes.